The Role of Intra-School Student Organization (OSIS) Membership in Friendships in High School - Aqila Humayda; Danish Asfa Durrani; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2025)
High school (SMA) is not only a forum for imparting knowledge but also a platform for students to develop soft and hard skills through organizational membership and activities. Organizations can provide a platform for students to develop non-academic abilities. The purpose of this study was to examine the role of Intra-School Student Organization membership in friendships in high school. The method used in this study was a literature review using Publish or Perish. 200 articles were obtained from Google Scholar, then 20 articles were sorted by title. The results of the literature review indicate that the Student Council (OSIS) plays a role in student friendships in high school. Through organizational activities such as deliberation meetings, leadership training, and collaborative project work, students' social skills can be involved and developed, forming stronger bonds within friendships. The OSIS is not only a forum for student character development but also a social catalyst, serving to expand relationships and strengthen the quality of student friendships.